Pollution Index Analysis and Water Pollution Control Strategy in Berenyok River, Tanjung Karang, Mataram City - M Said Ramdlan; Uzlifatul Azmiyati (Universitas Diponegoro, 2022)
Berenyok river is one of the water sources in Tanjung Karang, Mataram city, categorised as Class 2 for its designation. Thus, preserving the quality of water in the Berenyok river is crucial. This study aims to determine the water quality, calculate the Pollution Index (PI), and set control strategies for the Berenyok river. The study uses quantitative methods such as laboratory analysis for the water quality and PI calculation using a formula based on the Decree of the Minister of Environment No.115/2003 on determining water quality status. Meanwhile, the Strengths, Weakness, Opportunities, and Threats (SWOT) analysis generates recommendations for water pollution control strategies. The sampling locations are located in two sampling points (upstream and downstream of the Berenyok river) during bright daylight and the river's normal flow. Based on analysis results, the Berenyok river is defined as lightly polluted as the concentrations of several chemical parameters exceed the maximum limit, such as BOD, and PO3-P. It is also verified by high concentration of total coliform, namely 540,000 MPN/100mL (upstream) and 1,600,000 MPN/100mL (downstream). Thus, recommendations for water pollution control strategies are substantial for the Berenyok river.